The current status of the Korean student health examination - Hye-Jung Shin (Korean Pediatric Society, 2013)
Recent trends place an emphasis on school health care, the ultimate goal of which is to protect, maintain, and promote students' health. School health care is a program that integrates health care services, health education, health counseling, and local social health services. The student health examination (SHE) system is a part of school health care and schools and communities must be available to provide professional health services. Pediatricians also have important roles as experts in both school health care and the SHE system. In this article, the history of school health care, its legal basis, and the current status of the SHE system in Korea are reviewed. Furthermore, sample surveys from the past few years are reviewed. Through this holistic approach, future directions are proposed for the improvement of SHE and school health care.